All-optical nanoscopic spatial control of molecular reaction yields on nanoparticles - Zhang, Wenbin; Dagar, Ritika; Rosenberger, Philipp; Sousa-Castillo, Ana; Neuhaus, Marcel; Li, Weiwei; Khan, Sharjeel A.; Alnaser, Ali S.; Cortes, Emiliano; Maier, Stefan A.; Costa-Vera, Cesar; Kling, Matthias F.; et al. (Optica, 2022)
Molecular adsorbate reactions on nanoparticles play a fundamental role in areas such as nano-photocatalysis, atmospheric, and astrochemistry. They can be induced, enhanced, and controlled by field localization and enhancement on the nanoparticle surface. In particular, the ability to perform highly controlled near-field-mediated reactions is key to deepening our understanding of surface photoactivity on nanosystems. Here, using reaction nanoscopy, we experimentally demonstrate all-optical nanoscopic control of surface reaction yields by tailoring the near fields on nanoparticles with waveform-controlled linear and bicircular two-color laser pulses, respectively. We observe site-selective proton emission from the dissociative ionization of adsorbate molecules on SiO2 nanoparticles as a function of the polarization and relative phase of the two-color pulses. The angularly resolved close-to-uniform mapping between the surface reaction yields and the measured ion momentum enables the observation and spatial control of molecular reactions on the nanoparticle surface with nanoscopic resolution. The experimental results are modeled and reproduced qualitatively by classical trajectory Monte Carlo simulations. Our work paves the way toward reliable all-optical control of photocatalytic chemical reactions on nanoscale surfaces.
CRIS-Team Scopus Importer:2023-04-20